The Quality of the Parent–Child Relationship in the Context of Autism: The Role of Parental Resolution of the Child’s Diagnosis, Parenting Stress, and Caregiving Burden - Annalisa Levante; Chiara Martis; Flavia Lecciso (European Journal of Investigation in Health, Psychology and Education, 2025)
Background. Parents of autistic children face challenges that can negatively affect the quality of the parent–child relationship. This study aimed to explore the potential protective role of parental resolution about positive (closeness) and negative (conflict and dependence) aspects of the parent–child relationship, with parenting stress and caregiving burden as mediators. Methods. A cross-sectional study (ethical approval: CE n. 92949) was conducted with 51 Italian parents of autistic children. A multiple mediation model was tested. Results. Parental resolution had a significant total effect (β = 0.012; BootLLCI = 0.002; BootULCI = 0.024) and a significant direct effect on the parent–child relationship (β = 0.223; BootLLCI = 0.058; BootULCI = 0.389), indicating that resolving the child’s diagnosis could potentially influence parents’ perceptions of their relationship with their child, possibly leading to views of it being somewhat closer, experiencing fewer conflicts, and involving a lower degree of dependence. An indirect effect via parenting stress was also significant (β = −0.130; BootLLCI = −0.009; BootULCI = −0.291), while caregiving burden did not show a mediating effect. Conclusion: Despite the exploratory and cross-sectional nature of this study, the findings highlight the importance of promoting family well-being in the context of autism. The findings may inform future research on parental resources and guide clinicians in developing intervention programmes to mitigate the emotional impact of receiving a child’s autism diagnosis.